Civic education and defensive republicanism in France after the assassination of Samuel Paty - Szukala, Andrea (JSSE - Journal of Social Science Education, 2023)
Highlights: The assassination of Samuel Paty is an exceptional event that allows for multiple readings, but this presupposes that the facts and political processes surrounding the case are properly reconstructed. As presented, the study can be used as a starting point for further discussion and analysis around the question of educational governance of civic education in societies under stress. Purpose: The Samuel Paty murder has generated a great response from the professional community and the world of education and schools in Europe and worldwide. In a unique way, civic educators expressed horror, sorrow, and solidarity with the family and with their French colleagues. The article is dedicated to Samuel Paty and the question of whether and how we as a community of international civic educators can learn from this terrible event. Design/methodology/approach: The article presents a case reconstruction using press and public documents attempting to disentangle the actors’ positions, their stated intentions and contexts, and the following political intricacies of the case. Findings: The murder of Samuel Paty provoked a series of educational policy reactions that have paradoxical effects on civic education in schools, seen its intentions of political-social inclusion into a citizenship model. The case analysis documents the pitfalls of the instrumentalization of civic education for the securitization of societies.